BENTUK BUDAYA MELALUI KEHIDUPAN PRIBADI PRIYAYI DALAM NOVEL â€œCANTINGâ€KARYA ARSWENDO ATMOWILOTO - Indarawati, Ainur Trihana (Aksara Public, 2018)
This research reveals a cultural form that can be seen from the personal life of priyayi in the novel "Canting" by Aeswendo Atmawiloto. The researcher chose the novel "Canting" because of the rich values of Javanese culture by presenting the life of the priyayi. In addition, researchers also have other reasons because Arswendo Atmowiloto as an author has had achievements in getting awards from outside and within the country. The results of the analysis in Aeswendo Atmawiloto's "Canting" novel about the cultural forms of prijaji personal life include (1) wealth, (2) lifestyle, and (3) behavior.